(untitled) (Interdisciplinary Studies Journal, 2024)
This work is an excerpt from Magalhães’ (2021) dissertation. The aim of the research was to create and validate signs for terms related to Family Farming, which do not exist in LIBRAS, and to organize a bilingual glossary based on linguistic analyses in lexicographical records. To interpret the information collected and understand the meanings of the researched terminology, the study adopted a descriptive and interpretative research approach with a quantitative-qualitative focus, including statistical analysis of the terms and qualitative interpretation of the data. The methodological steps began with the selection of specific terms from Portuguese dictionaries, validated by a focus group from the Agricultural and Environmental Areas. Subsequently, the terms were researched in LIBRAS dictionaries and by bilingual professionals, with the creation of sign-terms proposed, which were validated by the local Deaf Association, interpreters, and LIBRAS professionals from the Amazon. As a result, fifty terms were cataloged, of which forty-four were created and six were identified as being in use by the Deaf community. The signs were compiled into a bilingual glossary, freely accessible in a repository at the University of São Paulo (USP), titled "Family Farming Terms in LIBRAS" - a tool for facilitating communication between Deaf people, professionals in related fields, and anyone interested.